Cash waqf as an alternative panacea to poverty alleviation: An overview of human development in Nigeria - Oladapo, Hakeem B.; Md Saad, Norma; Omar Mohamad, Mustafa; Oziev, Gapur (Islam Iktisadi Arastrima Merkezi (IKAM), 2017)
This study investigated how cash waqf was used to alleviate education poverty in Nigeria among the orphans and under-privileged in Zamfara State in particular. The failure of government has deprived people of good health, shelter, education among other things. Similarly, efforts of both private and voluntary sectors yielded no useful results especially in sponsoring students’ education. It is undeniable that poverty has become household problem in Africa and specifically Nigeria. The menace has deprived people of basic necessity of life hence, throw them into serious predicament. The present study used qualitative technique hence, conducted in-depth interviews of three types of respondents. Data gathered from the interview was analyzed using a phenomenological approach. It is hoped that the findings will be useful to policy makers in waqf institutions and the Nigerian government to strategize poverty alleviation inclusive of orphans and under-privileged education in order to boost the level of literacy in the country.